An Overview of Parents' Stress Levels when Accompanying Online Learning for Students - Dewi Purnama Windasari; Muh. Sahlan Zamaa; Iskandar Zulkarnaen; Hardiansyah Hardiansyah (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
More than 800 million students in the world are learning at home as a result of the covid-19 pandemic. The transition of face-to-face learning to Study From Home (SFH) makes the role of parents very influential in supporting children's success in undergoing online learning systems. Such critical conditions make parents overwhelmed in balancing the role of being a teacher for children at home and also the demands of being a parent which ultimately triggers stress. This study intends to find out an overview of the stress level of parents of elementary school students in online learning in Batua Raya Village, Makassar City. This research is a descriptive study. The population in this study was parents who had elementary school children who carried out online learning as many as 375 students with a total sample of 67 people with a sampling technique in this study was purposive sampling This research used a questionnaire as an instrument for collecting research data. The results of this study found that respondents who had moderate stress totaled 22 people (32.8%) and respondents who had mild stress totaled 45 people (67.2%). The conclusion from the study, that respondents in this study experienced more mild stress. It is recommended that respondents can make interventions related to controlling the stress experienced.